Pengaruh Kepemimpinan Kepala Sekolah Dan Peran Komite Sekolah Terhadap Keberhasilan Manajemen Berbasis Sekolah Di SMK Negeri Sekecamatan Kayuagung - Sarwani Ahmad; Wahyudi, Wahyudi; Suherman, Suherman (CV. Ulil Albab Corp, 2025)
This study aims to determine and analyze: (1) The influence of principal leadership on the success of school-based management; (2) The influence of school committees on the success of school-based management; and (3) The influence of principal leadership and school committees together on the success of school-based management. This study is a quantitative study with a partial correlation method. This study was conducted at State Vocational High Schools in Kayuagung District with 134 teachers as respondents. Data collection techniques used questionnaires and documentation. The validity test used construct validity while the reliability test used Cronbach's Alpha. The prerequisite test of the analysis used the normality test, homogeneity test, and linearity test, and the data was analyzed using simple regression and multiple regression techniques. The results of the study showed that: (1) There is a significant influence between the principal's leadership on the success of school-based management. This is indicated by the t-count value (240.536) ≥ t-table (1.656). (2) There is a significant influence between the school committee on the success of school-based management. This is indicated by the t-count value (34.655) ≥ t-table (1.656). (3) There is a significant influence between the principal's leadership and the committee on the success of school-based management. This is indicated by the f-count value (5.786) ≥ f-table (3.07).